Intranasal Corticosteroid Spray Usage in Patients with Allergic Rhinitis: Correctness in Technique and Compliance - Gurung, Urmila; Khadgi, Sajish (Journal of Institute of Medicine Nepal, 2024)
Introduction Intranasal corticosteroid spray (INCS) needs to be administered correctly and regularly for it to be effective in treating allergic rhinitis. This study aimed to assess the correctness of technique and compliance of intranasal corticosteroid spray usage in patients with allergic rhinitis. Methods It was a cross-sectional study conducted in the Dept of ENT-Head and Neck surgery, Tribhuvan University Teaching Hospital from April to September 2023. Patients aged 18 or more with allergic rhinitis on INCS or had been on INCS in the past three months were assessed for INCS administration technique based on EPOS 2020 checklist and their compliance asked. Factors that could hinder the correct techniques and compliance were assessed. Results A total of 138 patients, 71 males and 67 females, aged 18 to 55 years were included. Most of them (60/138; 43.5%) had completed secondary level education. 97.1% (134/138) had been prescribed INCS spray by ENT doctor and 89.13% (124/ 138) had received verbal instructions mostly by ENT doctor (91.1%). 7.2% (10/138) completed all the steps as per EPOS 2020 checklist whilst 25/138 (18.1%) completed five essential steps. The correctness of the INCS administration technique however did not differ with age, gender, academic qualification, prescriber or whether instructions were given or not. 119/138 (86.2%) patients reported being compliant. Conclusion INCS spray was scarcely administered with the correct technique although the compliance was good. This study emphasizes the need for effective patient and healthcare worker education pertaining to correct INCS technique.